DINAMIKA POLITIK GLOBAL DALAM ERA MULTIPOLAR: TANTANGAN DAN PELUANG BAGI NEGARA BERKEMBANG - Iwan Gunawan (Journal of Economic, Bussines and Accounting (COSTING), 2023)
In the current multipolar era, developing countries face various challenges and opportunities in dynamic global politics. This research aims to analyze the main challenges facing developing countries in a multipolar system, such as economic dependence on developed countries, external political pressure, and alliance dilemmas in great power competition. In addition, this research also highlights the strategic opportunities available, including the formation of alliances, participation in international organizations, and the use of soft power to strengthen bargaining positions. Through theoretical analysis that combines the perspectives of realism, liberalism, and sustainable development theory, this research emphasizes the importance of diplomatic capacity, investment in technological development and human resources, as well as the role of regional institutions as supporters of stability and cooperation. The research results recommend a proactive, holistic strategic approach for developing countries to strengthen their position in international politics, without sacrificing sovereignty. It is hoped that these findings can contribute to international relations literature and serve as a guide for policy makers in designing adaptive and competitive diplomatic strategies amidst increasingly complex multipolar competition.